2022
DOI: 10.1155/2022/5160876
|View full text |Cite
|
Sign up to set email alerts
|

Field Pull-Out Test and Analysis of Fiberglass Anchors in Sanshandao Gold Mine

Abstract: The Sanshandao gold mine is developed near the sea and has high-chloride ion content in the groundwater, resulting in serious corrosion of metal anchors and difficulty in maintaining metal anchors. To solve the corrosion problem of anchor rods in Sanshandao, the use of fiberglass anchor rods, instead of metal anchor rods, is proposed. To verify the feasibility of fiberglass anchor application, a fiberglass anchor (diameter: 27 mm) pulling test was conducted at the Sanshandao gold mine. The test results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A conventional sidewall transparent pullout box can only observe particle movement at the edge of the soil inside the box; this does not reflect the internally reinforced soil interaction during the pullout process. Experimental studies have shown that the apparent friction angle in the pullout test is positively related to the interface friction angle between the front wall of the pullout box and the fill soil (Christian et al, 2022;Ren et al, 2022;Wang et al, 2022). The friction between the front wall and the soil is larger, so the observation of the soil near the front wall should be avoided, and a large pullout box should be selected as much as possible (Konstantin et al, 2022;Zhao et al, 2022).…”
Section: Testing Programmentioning
confidence: 99%
“…A conventional sidewall transparent pullout box can only observe particle movement at the edge of the soil inside the box; this does not reflect the internally reinforced soil interaction during the pullout process. Experimental studies have shown that the apparent friction angle in the pullout test is positively related to the interface friction angle between the front wall of the pullout box and the fill soil (Christian et al, 2022;Ren et al, 2022;Wang et al, 2022). The friction between the front wall and the soil is larger, so the observation of the soil near the front wall should be avoided, and a large pullout box should be selected as much as possible (Konstantin et al, 2022;Zhao et al, 2022).…”
Section: Testing Programmentioning
confidence: 99%